Effect of post-weaning level of nutrition on the early reproductive performance and productivity indices of Menz sheep - Mukasa-Mugerwa, E.; Negussie, A.; Said, A.N. (Informa UK Limited, 1994)
Weaner ewe lambs (92 + 4 days, SD) of the Ethiopian Menz breed (n=115) were used to assess the impact of level of nutrition before and after first lambing on subsequent productivity. Lambs were raised either on pasture grazing only (P) or grazing with low (L), medium (M) or high (H) levels of a concentrate supplement containing 125 g/kg DM digestible protein and 25 Mcal/kg DM. Postweaning mortality was 13.9 percent being substantially higher for P animals (33 percent) than better fed counterparts (7 percent). Lamb weaning weight was affected by lambing season (P<0.01) and ewe postpartum level of nutrition (P<0.05). Both factors also affected the three productivity indices expressed as (1) the weight of a 90 days old lamb produced per ewe per year (Index I), (2) per kg of breeding female per year (Index II) or (3) per kg 0.73 of breeding female per year (Index III), and respectively averaging 11.0 + 0.87 kg., 520 + 41 g and 1.18 + 0.09 kg. The productivity index for ewes that only grazed was estimated as 60 and 50 percent that of contemporaries on L and M dietary levels because of lower lamb weaning rates, slower growth and extended lambing intervals. A possible approach to improve productivity of Menz sheep is suggested.